2003
DOI: 10.1042/bst0310960
|View full text |Cite
|
Sign up to set email alerts
|

Agonist-induced calcium and oxidative stress responses in endothelial cells

Abstract: [Ca(2+)](i) (cytosolic [Ca(2+)]) and OS (oxidative stress) were measured simultaneously in calf pulmonary artery endothelial cells using fura-2 and carboxy-2',7'-dichlorodihydrofluorescein. ATP stimulated a [Ca(2+)](i) increase that was followed a few seconds later by an increase in OS. Pre-exposure to 5 microM H(2)O(2) potentiated these responses to ATP. Elevating or removing extracellular Ca(2+) increased or reduced the [Ca(2+)](i) response to ATP and caused parallel changes in the OS response, suggesting th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Furthermore, Steinert et al (2002) and Mahdy et al (1998) demonstrated that human fetal venous EC and maternal human hand vein EC show a loss of the sustained phase in subjects with preeclampsia, a condition that is characterized by hypertension (Mahdy et al 1998, Steinert et al 2002. This data along with our previous data on UAEC led us to believe that the sustained phase of the [Ca 2C ] i response in NP-UAEC is relatively unresponsive, while P-UAEC mobilize Ca 2C more like calf pulmonary artery EC, bovine aortic EC, and rat aortic EC (Chu et al 2000, Bishara et al 2002, Wilkinson & Jacob 2003.…”
Section: Introductionmentioning
confidence: 71%
“…Furthermore, Steinert et al (2002) and Mahdy et al (1998) demonstrated that human fetal venous EC and maternal human hand vein EC show a loss of the sustained phase in subjects with preeclampsia, a condition that is characterized by hypertension (Mahdy et al 1998, Steinert et al 2002. This data along with our previous data on UAEC led us to believe that the sustained phase of the [Ca 2C ] i response in NP-UAEC is relatively unresponsive, while P-UAEC mobilize Ca 2C more like calf pulmonary artery EC, bovine aortic EC, and rat aortic EC (Chu et al 2000, Bishara et al 2002, Wilkinson & Jacob 2003.…”
Section: Introductionmentioning
confidence: 71%
“…Binding of EPO to its receptor causes a rise of intracellular calcium levels (30) and thereby inhibits NO production and eNOS protein expression in endothelial cells (7). Recently, it was reported that ATP-stimulated cytosolic calcium increase is followed by an increase in ROS formation in endothelial cells (31).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was reported that agonist-stimulated cytosolic calcium increase is followed by an increase in ROS formation in endothelial cells. 36 Because TRPC5 channels are calcium permeable, elevated agonist-stimulated calcium influx through upregulated TRPC5 channels in endothelial cells during EPO treatment may contribute to the ROS formation, which underlies pathogenesis of EPO-induced hypertension.…”
Section: Discussionmentioning
confidence: 99%